Effects of Whey Peptides on the Quality of Pork Ball Preprepared Dishes during Repeated Freezing–Thawing - Xiaotong Zhang; Pengjuan Yu; Jiayan Yan; Yishuang Shi; Jianhui Feng; Xinyan Peng (Foods, 2023)
This study evaluated the effect of FI (Fraction I, molecular weight < 1 kDa), which is separated from natural whey protein, on the antioxidant activity, sensory quality, color, texture characteristics, and microbial growth of pork balls during repeated freeze–thaw cycles (F-T cycles). The results indicated that pork balls mixed with FI significantly improved in quality after repeating the F-T cycle, especially with the addition of 10% FI. The quality was improved significantly after repeated F-T cycles by adding 10% FI, and the antioxidant activity after seven F-T cycles decreased by 40.78%, a similar result to that obtained with the addition of 0.02% BHA. In addition, FI effectively reduced the sensory damage of pork balls caused by repeated freezing–thawing and also significantly inhibited the growth of microorganisms. In summary, FI not only has excellent antioxidant capacity under repeated freeze–thaw conditions but also has significant antibacterial and quality preservation effects and is expected to be quantified as a kind of natural food additive with antibacterial and antioxidant properties. This paper not only explores the effect of FI on the quality characteristics of frozen and thawed pork balls in prepared dishes but also provides a theoretical basis for the application of whey polypeptides in prepared meat.